2014
DOI: 10.1063/1.4880938
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Néel temperature of magnetoelectric chromia for voltage-controlled spintronics

Abstract: Boron doped chromia (Cr2O3) thin films with substitutional doping levels between zero and 3% are grown using pulsed laser deposition in borane background gases. Magnetometry reveals a tunable increase in the Néel temperature of the (0001) textured Cr2BxO3−x thin films at a rate of about 10% with 1% oxygen site substitution preserving a net boundary magnetization. Spin resolved inverse photoemission measured after magnetoelectric annealing in subsequently reversed electric fields evidences voltage-controlled re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 28 publications
3
61
0
Order By: Relevance
“…15 They reported that 1% substitution of boron at the oxygen sites can enhance T N by 10%, without destroying the AFM ordering in Cr 2 O 3 . Experimentally, Street et al 16 confirmed the enhancement of T N in chromia thin films fabricated by pulsed laser deposition from a Cr 2 O 3 target in a decaborane (B 10 H 14 ) gas environment. However, doping at anion sites will be difficult because B prefers the trivalent B 3þ state.…”
Section: Introductionmentioning
confidence: 90%
“…15 They reported that 1% substitution of boron at the oxygen sites can enhance T N by 10%, without destroying the AFM ordering in Cr 2 O 3 . Experimentally, Street et al 16 confirmed the enhancement of T N in chromia thin films fabricated by pulsed laser deposition from a Cr 2 O 3 target in a decaborane (B 10 H 14 ) gas environment. However, doping at anion sites will be difficult because B prefers the trivalent B 3þ state.…”
Section: Introductionmentioning
confidence: 90%
“…In order to suppress these noise sources, it was necessary to measure the magnetic signal in the complete absence of any applied magnetic field, a condition that was achieved by quenching [28] the superconducting magnet of our magnetometer prior to every measurement sequence. Correspondingly, we have utilized a rather specific T and H dependent measurement protocol, consisting of a zero field heating (ZFH) magnetization measurement sequence, starting at T = 100 K and followed up to T = 350 K, after first high-field cooling (FC) the sample from T = 350 K down to T = 100 K. Details of this measurement procedure have been published elsewhere [12,13,29]. Fig.7 shows the resulting temperature dependence of the out-ofplane remnant magnetic moment m for the entire set of our epitaxial Cr (2-x) Al (x) O 3 alloy films after prior FC in an applied magnetic field of μ 0 H = 7 T. All data show a positive magnetization value at low temperature due to the positive magnetic field applied during FC, which leads to the selection of a state with positive BM.…”
Section: B Magnetic Characterizationmentioning
confidence: 99%
“…For such a spin FET to actually work, based on the induced polarization from the gate, the device requires a dielectric gate with interface polarization in proximity to the graphene. Most promising would be a nonvolatile spin-FET, with a multiferroic or magnetoelectric gate dielectric, having high interface polarization like chromia , where the interface polarization can be controlled by voltage , He 2010, Street 2014. There have already been several efforts to investigate the induced magnetism or spin polarization in graphene supported on magnetic insulators.…”
mentioning
confidence: 99%